Feminicide from the perspective of the cultural mediation of information - Cavalcante, Luciane de Fátima Beckman (Advanced Notes in Information Science, 2023)
Femicide is the extreme crime that results from a set of violence suffered by women, characterized by murder that involves domestic and family violence, contempt or discrimination against the condition of woman, being considered a heinous crime. Based on the bibliographic research method, this exploratory research aims to understand femicide in a reading key that involves culturally and informationally mediated constructions in social relations. The results point to the existence of a process historically rooted in a patriarchal culture and gender inequality, which sees women as an object of domination and use, whether for domestic, economic and/or sexual purposes. In this sense, cultural mediation of information is presented as a possible tool, within the scope of studies that understand mediation as an action of interference, for the deconstruction of such cultural stereotypes, in order to contribute to the fight against crimes of femicide and violence against women.